Bahan Styrofoam Sebagai Ekspresi Penciptaan Seni Patung di Rumah Gabus Produktion Surabaya - Totok Priyoleksono; Mohamad Arifin; Pangeran Pandularas (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2023)
Most people only think that styrofoam is a material for packaging tools, for example as a container to store ice, a protector of electronic objects so that they are not damaged by vibration. According to Nanang Muchsinien, the advantage of using styrofoam as a creative medium is that it can be made in a shorter time than other materials, such as wood, cement, or other materials. The character of styreofoam which is not so heavy or relatively light, and has a small risk; therefore, using stereofoam material is not dangerous in the event of a work accident if it is hit, or falls when installed in public places Some other supporting facilities are: adequate space, tools, and materials, and of course styreofoam with good quality as the main medium styreofoam or foam plastic is one type of plastic from many other materials. The first is to make a sketch on paper as a means to find out the division of the image pieces from the existing design. The process of smoothing for this work is done by rubbing the surface of the styreofoam with rubbing paper. Technology for working on styreofoam materials is needed to speed up working so that the production process is more efficient, can save time, energy, and can reduce costs. The modeling process is carried out using modeling techniques so that in creating a sculpture that can interact directly between ideas into three dimentional form (sculpture art). In choosing to use cork/ styrofoam material because the material has already found the character of the material and the properties that exist in the material, so that it can speed up the creative process.